Concurrent transmission of multiple carbapenemases in a long-term acute-care hospital - Rankin, Danielle A.; Walters, Maroya Spalding; Caicedo, Luz; Gable, Paige; Moulton-Meissner, Heather A.; Chan, Allison; Burks, Albert; Edwards, Kendra; McAllister, Gillian; Kent, Alyssa; Laufer Halpin, Alison; Moore, Christina; et al. (Infection control and hospital epidemiology, 2024)
We investigated concurrent outbreaks of carrying (VIM-CRPA) and Enterobacterales carrying (KPC-CRE) at a long-term acute-care hospital (LTACH A). We defined an incident case as the first detection of or from a patient's clinical cultures or colonization screening test. We reviewed medical records and performed infection control assessments, colonization screening, environmental sampling, and molecular characterization of carbapenemase-producing organisms from clinical and environmental sources by pulsed-field gel electrophoresis (PFGE) and whole-genome sequencing. From July 2017 to December 2018, 76 incident cases were identified from 69 case patients: 51 had 11 had and 7 had and . Also, were identified from 7 Enterobacterales, and all were . We observed gaps in hand hygiene, and we recovered KPC-CRE and VIM-CRPA from drains and toilets. We identified 4 KPC alleles and 2 VIM alleles; 2 KPC alleles were located on plasmids that were identified across multiple Enterobacterales and in both clinical and environmental isolates. Our response to a single patient colonized with VIM-CRPA and KPC-CRE identified concurrent CPO outbreaks at LTACH A. Epidemiologic and genomic investigations indicated that the observed diversity was due to a combination of multiple introductions of VIM-CRPA and KPC-CRE and to the transfer of carbapenemase genes across different bacteria species and strains. Improved infection control, including interventions that minimized potential spread from wastewater premise plumbing, stopped transmission.